OPTIMIZATION OF THE ASSIGNMENT OF EMPLOYEES THROUGH HUNGARIAN METHOD - Mubarak, Husni; Bahri, Syamsul; Hinnai, Silvi; Hidayat, Rahmat (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2024)
The purpose of this research is to optimally assign employees with different costs and types of work using the Hungarian method. This research was conducted on 10 employees in one of the delivery service companies in Medan City in 2024. The steps used to perform optimal employee assignment are: create an assignment cost table, perform cost reduction on each row, perform cost reduction on columns that have no zero value, and make optimal assignments. The results of this study provide an optimal solution to the employee assignment problem, therefore, the use of this method is highly recommended to solve employee assignment problems in companies